COUNSELING GUIDANCE HANDLING OF HYPERACTIVE CHILDREN - Faza Ida Nurul Jannah; Viviana Nisful Laili; Avicarizta Zunia Avinda; Ahmad Ipmawan Kharisma (Universitas Muhammadiyah Lamongan, 2024)
The background of the teacher's role in dealing with hyperactive children includes the teacher being a motivator, advisor as well as the teacher being a facilitator for children during learning. Hyperactive children tend not to want to be quiet and always run everywhere, disturbing their friends and others. The purpose of this study examines how the role of the teacher in dealing with hyperactive children. This research uses descriptive qualitative research. The instruments of this research are teacher interviews and student observations. In this study also found several teacher techniques in dealing with hyperactive children, namely (1) by giving assignments to children so that the child has a sense of responsibility. (2) the teacher gives praise to hyperactive children if they complete the tasks given by the teacher. (3) the teacher also provides active activities for hyperactive children. The conclusion of this study is that the teacher has provided maximum counseling guidance to hyperactive children. Suggestions to further researchers can conduct research in other places.